Diagnostics of interstellar medium parameters on non-discrete timing irregularities of pulsars - U. Iyida, E.; I. Eze, C. (International Journal of Advanced Astronomy, 2021)
In this paper, a large homogenous sample of Jodrell Bank Observatory (JBO) radio pulsars was used to investigate the statistical effects of interstellar medium (ISM) parameters: dispersion and rotation measure (DM and RM, respectively) on non-discrete timing irregularities of our sample (whose observed timing activity timescales span over 40 years). This is done by using the correlations between the measured DM and RM, and some parameters that have been commonly used to measure non-discrete timing irregularities [timing activity parameter (A), the amount of timing fluctuations absorbed by the cubic term (ÏƒR23), measure of pulsar rotational stability (Ïƒz ) and stability parameter (âˆ†8)]. Our results show that ISM parameters positively correlate (r > 0.60) with the pulsar timing irregularities parameters of our sample. The significant relationships observed are discussed.Â Â
Keywords: Methods; Statistical; Pulsars; General; Interstellar Medium; General.